2010
DOI: 10.1080/10426501003713080
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphine-Catalyzed Preparation of Sterically Congested, Electron-PoorN-Vinylimidazole Derivatives from Acetylenic Esters and Imidazole-Containing NH-Acids

Abstract: Protonation of the highly reactive 1:1 intermediates, produced in the reaction between triphenylphosphine and alkyl acetylenecarboxylates (or ethyl 3-phenyl-2-propynoate), by azathioprine or imidazole leads to vinyltriphenylphosphonium salts, which undergo a Michael addition reaction with a conjugate base to produce phosphorus ylides. Dipotassium hydrogen phosphate, potassium dihydrogen phosphate, and potassium iodide were found to catalyze the conversion of the phosphorus ylides to electron-poor N-vinyl imida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…N ‐Vinylation of purines with vinyl acetate and Hg(OAc) 2 may give the 7‐vinylisomer as a by‐products in low yields 7. It was recently reported that azathioprine reacts with esters of acetylenecarboxylates in the presence of PPh 3 to give only the N ‐7‐alkenylated Michael‐type adducts 16. We have shown that the N ‐7 allyl group in N 6 , N ‐7‐diallyladenine can be selectively rearranged to propenyl and used the product in an RCM‐mediated synthesis of the heterocyclic part of asmarines (marine bioactive natural products) 17.…”
Section: Introductionmentioning
confidence: 95%
“…N ‐Vinylation of purines with vinyl acetate and Hg(OAc) 2 may give the 7‐vinylisomer as a by‐products in low yields 7. It was recently reported that azathioprine reacts with esters of acetylenecarboxylates in the presence of PPh 3 to give only the N ‐7‐alkenylated Michael‐type adducts 16. We have shown that the N ‐7 allyl group in N 6 , N ‐7‐diallyladenine can be selectively rearranged to propenyl and used the product in an RCM‐mediated synthesis of the heterocyclic part of asmarines (marine bioactive natural products) 17.…”
Section: Introductionmentioning
confidence: 95%